The Education Model According to Technology Disruption in Thailand: Private University - Panjaphon Petrapoonsinchai (Journal of Humanities and Social Sciences Mahasarakham University, 2022)
The objectives of this study are to find the patterns, significances, effects, and results of technology disruption in the Thailand higher education system. The results will be used as guidelines for designing an educational approach which uses various technologies in the Thai higher education system. The research methodologies werein-depthinterviews with the instructors and educational staff, totalling 26 people, participant observation and group discussion with 38 students. It was found that the teaching and learning model in Thailand’s higher education has continued to use technology as a tool for teaching and learning, practicing, as well as an online teaching channel during the COVID-19 crisis.This was the importance of technology that reduces the gap in education access and drives teaching and learning continuously, which has resulted in major changes ineducationpolicy, learning and teaching style, and the adaptation of learners. The results of the change in the teacher’s role, the qualification of learners, the teaching process, content, and assessment will require major improvements. All of these will influence the future of higher education teaching in Thailand, such as developing a highly flexible curriculum which can be adjusted to meet the needs of individual learners, a new learning culture based on a growth mindset, and the artificial intelligence system will become a personal teacher.